UJI EFEKTIVITAS ANTIBAKTERI SEDIAAN SABUN MANDI CAIR MINYAK ATSIRI KULIT BUAH JERUK PONTIANAK (Citrus nobilis Lour. Var. microcarpa) TERHADAP Staphylococcus aureus dan Escherichia coli - ., Risky Rosdiyawati (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Infection can caused by the pathogenic bacteria like Staphylococcusaureus and Escherichia coli. Synthetic antibacterial compounds could preventinfection but also had side effect,for example irritation. This became a trigger toproduced another product based on nature. Essential oil from Pontianak orangepeel (Citrus nobilis Lour. var. microcarpa) that contain antibacterial activity couldbe used to formulate the product. The purpose of this research was to know theeffectiveness of antibacterial activity of liquid soap from essential oil of Pontianakorange peel againts Staphylococcus aureus and Escherichia coli using discdiffusion method. This research was conducted with experimental method andused variation of essential oil concentration such as FI (0,05%); F2 (0,15%);F3(0,25%). The liquid soap then got physical and chemistry analysis such asorganoleptic, foaming power, density, viscosity, pH, and total fatty acids and alsoirritation test. The results of the research showed that the three formulas of liquidsoaps fulfill SNIâ€™s standard of liquid soaps, not cause irritation and also showedbest effectiveness at F1 (0,05%) with 7,17 mm zone of inhibition ofStaphylococcus aureus and 18,59 mm zone of inhibitionÂ of Escherichia coli.Keywords: antibacterial, essential oil of Pontianak orange peel, liquid soap